2012
DOI: 10.1371/journal.pone.0031089
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Striatum and Its Limbic Connectivity Mediate Abnormal Anticipatory Reward Processing in Obesity

Abstract: Obesity is characterized by an imbalance in the brain circuits promoting reward seeking and those governing cognitive control. Here we show that the dorsal caudate nucleus and its connections with amygdala, insula and prefrontal cortex contribute to abnormal reward processing in obesity. We measured regional brain glucose uptake in morbidly obese (n = 19) and normal weighted (n = 16) subjects with 2-[18F]fluoro-2-deoxyglucose ([18F]FDG) positron emission tomography (PET) during euglycemic hyperinsulinemia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(187 citation statements)
references
References 57 publications
10
175
0
2
Order By: Relevance
“…This may be of particular concern in relation to the development and maintenance of obesity given the association between consumption of high energy-dense foods and subsequent weight gain (46)(47)(48) . These findings also reflect results from recent neuroimaging studies (49)(50)(51)(52)(53) that demonstrated greater activation of reward pathways in the brain on exposure to high energy-dense food images. Coupled with attentional bias studies, these neuroimaging studies provide a further insight into how eating behaviours may be affected by potential dysregulation in areas of the brain involved in processing the rewarding properties of foods.…”
Section: Effects Of Energy Density Of Food-related Cuessupporting
confidence: 86%
“…This may be of particular concern in relation to the development and maintenance of obesity given the association between consumption of high energy-dense foods and subsequent weight gain (46)(47)(48) . These findings also reflect results from recent neuroimaging studies (49)(50)(51)(52)(53) that demonstrated greater activation of reward pathways in the brain on exposure to high energy-dense food images. Coupled with attentional bias studies, these neuroimaging studies provide a further insight into how eating behaviours may be affected by potential dysregulation in areas of the brain involved in processing the rewarding properties of foods.…”
Section: Effects Of Energy Density Of Food-related Cuessupporting
confidence: 86%
“…Postprandially, AA and TT subjects exhibited a differential relationship between postprandial acyl-ghrelin suppression and BOLD responses to food-related images within brain regions involved in visual attention and in encoding visual cue incentive value (44) and integrative/executive decision making. In addition, divergent acyl-ghrelin suppression and BOLD responses to hedonic food cues were observed within the right caudate nucleus, a region implicated in controlling incentive motivation, anticipatory food reward, and food craving (45). Collectively, these results show that the FTO genotype alters CNS responsivity to circulating ghrelin levels.…”
Section: Figurementioning
confidence: 72%
“…This effect was driven by a positive relationship between the BOLD response within these regions and meal-induced acyl-ghrelin suppression in the TT subjects, while the AA subjects displayed a negative relationship (Figure 4, E and F). In response to high-calorie images, the AA and TT subjects exhibited a significantly divergent response within the right caudate nucleus (z = 3.91 [22,8,18]) ( Figure 4G), a brain region that controls incentive motivation and that has been shown to exhibit an increased BOLD response to hedonic food images in obese compared with normal-weight subjects (45). In AA subjects, the BOLD response within the caudate was positively related with postprandial acyl-ghrelin suppression, whereas in TT subjects, a negative relationship was observed (Figure 4, H and I).…”
Section: Figurementioning
confidence: 99%
“…Increased amygdala responses to food cues in obese compared to healthy-weight individuals is one of the most replicated findings in the neuroimaging of obesity (e.g., [111,113]; see [16] for a review), including in children (e.g., [14]). External food sensitivity, i.e.…”
Section: Amygdala and Cue-induced Feedingmentioning
confidence: 94%